2004
DOI: 10.1165/rcmb.2003-0229oc
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive Transfer of Alveolar Macrophages Abrogates Bronchial Hyperresponsiveness

Abstract: Increasing evidence suggests that alveolar macrophages (AM) are involved in asthma pathogenesis. To better understand the role that these cells play, we investigated the capacity of AM from allergy-resistant rat, Sprague Dawley (SD), to modulate airway hyperresponsiveness of allergy-susceptible rat, Brown Norway (BN). AM of ovalbumin (OVA)-sensitized BN rats were eliminated by intratracheal instillation of liposomes containing clodronate. AM from OVA-sensitized SD rats were transferred into AM-depleted BN rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
78
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 31 publications
11
78
0
1
Order By: Relevance
“…Although they are well known to suppress T cell activation and antigen presentation activities of dendritic cells (22,41), their role in asthma is still debated. Using the liposome-mediated macrophage suicide technique (47), we have demonstrated that AM depletion of allergen-sensitized animals leads to airway hyperresponsiveness after allergen challenge (7). These data suggest that AM are essential for the prevention of airway hyperresponsiveness development.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Although they are well known to suppress T cell activation and antigen presentation activities of dendritic cells (22,41), their role in asthma is still debated. Using the liposome-mediated macrophage suicide technique (47), we have demonstrated that AM depletion of allergen-sensitized animals leads to airway hyperresponsiveness after allergen challenge (7). These data suggest that AM are essential for the prevention of airway hyperresponsiveness development.…”
mentioning
confidence: 80%
“…Group 1 represents the negative and positive controls, whereas group 2 was used to verify the effect of AM depletion using clodronate (Cl 2MDP; Sigma Chemical)-liposomes 17 days after sensitization (47). AM transfer (groups 3 and 4) was performed as previously described (7). Briefly, bronchoalveolar lavage (BAL) was done 20 days after sensitization, and 2 ϫ 10 6 cells were transferred by intratracheal intubation to rats that had received Cl 2MDP-liposomes 3 days earlier using the same technique.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas DC activate T cells and thereby promote inflammation, pulmonary M⌽ suppress these processes (20,21,37,43). It has therefore been suggested that the balance of these two cell types influences the progression of lung inflammation, such as asthma (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Adoptive transfer of macrophages has also been investigated in colitis and airway hyperresponsiveness, with promising results (51,52). Litvack and colleagues also showed that, although not true AMs, stem cell-derived, alveolar-like macrophages improved bacterial and neutrophil clearance in another model of lung injury (49), but further study is required to determine the safety and feasibility of these treatment modalities.…”
Section: Original Articlementioning
confidence: 99%